Corrosion protection of AZ31 magnesium alloy treated with La3＋ modified 3-methacryloxypropyltrimethoxysilane conversion film - 乔英杰 李文鹏 王桂香 张晓红 (Journal of rare earths, 2015)
This study demonstrated the influence of addition concentration of La3＋ on the anti-corrosion behavior of a 3-methacry- loxypropyltrimethoxysilane （MPS） film formed on AZ31 magnesium alloy. The morphology and surface chemistry of the samples were evaluated through scanning electron microscopy （SEM） and Fourier transform infrared spectroscopy （FT-IR）, respectively. The corrosion resistance of the pre-treated AZ31 magnesium alloy was studied during immersion in 0.1 mol/L NaC1 solution, using poten- tiodynamic polarization curves and electrochemical impedance spectra （EIS）. In comparison to MPS film, the low concentration of La3＋ ion modified silane layer exhibited a better anti-corrosion performance, nevertheless, the high concentration of La3＋ ion modified was worse. Results showed that the preferable addition concentration of La3＋ ion in the silane film was 5Х 10-4 mol/L in this experi- ment.